The Effectiveness Of Corporate Social Responsibility At Energy Equity Epic Sengkang Pty. Ltd - Najeminur Najeminur; Andi Supriadi; Herdi Syam (STIE PGRI Dewantara Jombang, 2021)
Abstract The effectiveness of the corporate social responsibility (CSR) program in indonesia still needs to be improved. It can be seen from the number of companies that make csr programs only a formality obligation without thinking about how much the benefits of the program are implemented for the community and the environment. This article discussed the effectiveness of corporate social responsibility at Energy Equity Epic Sengkang Pty. Ltd In Gilireng Sub-District, Wajo District, Which was analyzed using indicators of goal achievement, integration, and adaptation. The research method used was a qualitative approach with data collection techniques through literature review, observation and interviews, then analysis and data processing were carried out using reduction techniques and relevant data grouping. The results of the research were presented using descriptive techniques in the corporate social responsibility program at Energy Equity Epic Sengkang Pty. Ltd. Implemented by first communicating, coordinating, and socializing with the government and the community. The areas of CSR implementation are education, health, economy, public facilities, and the environment. CSR programs implemented meet effectiveness indicators, namely goal achievement, integration, and adaptation.